Description of Three New Genera of Metopidae (Metopida, Ciliophora): Pileometopus gen. nov., Castula gen. nov., and Longitaenia gen. nov., with Notes on the Phylogeny and Cryptic Diversity of Metopid Ciliates - Bourland, William; Rotterová, Johana; Čepička, Ivan (Protist, 2020)
We report the discovery of three new species of freshwater metopid ciliates, Pileometopus lynni gen. et sp. nov., Castula flexibilis gen. et sp. nov., and Longitaenia australis gen. et sp. nov. Based on morphologic features and the 18S rRNA gene phylogeny, we transfer two known species of Metopus to the new genus Castula, as C. fusca (Kahl, 1927) comb. nov. and C. setosa (Kahl, 1927) comb. nov. and another known species is herein transferred to the new genus Longitaenia, as L. gibba (Kahl, 1927) comb. nov. Pileometopus is characterized by a turbinate body shape, a dorsal field of densely spaced dikinetids, a bipartite paroral membrane, and long caudal cilia. A distinctive morphologic feature of Castula species is long setae arising over the posterior third of the body (as opposed to a terminal tuft). Longitaenia spp. are characterized by an equatorial cytostome and long perizonal ciliary stripe relative to the cell length. Based on phylogenetic analyses of 18S rRNA gene sequences, we identify and briefly discuss strongly supported clades and intraspecific genetic polymorphism within the order Metopida.
Keywords: fylogeografie; Phylogeny; 18S rRNA gene.; biogeography; phylogeny; RNA ribozomální 18S; Armophorea; Ciliophora; protargol impregnation; sladká voda; anaerobic ciliates; Fresh Water; Phylogeography; fylogeneze; RNA, Ribosomal, 18S